CSR Communication in Problematic Sectors: The Example of Hungarian Brewers - Majláth, Melinda; Ricordel, Pascal (European Journal of Sustainable Development, 2019)
Thesis statement: CSR reputation indices (like MSC KLD400, Dow Jones Sustainability Index) exist in such form which exclude companies operating in ethically questionable industries like tobacco, gambling, nuclear power, adult entertainment or alcoholic drinks. However, drinking alcohol is a very important part of the culture and is a tradition in many European countries (for socializing and as a gift) even if in some cases it has very ambivalent judgment. Alcohol addiction, domestic violence, traffic accidents, serious health problems mean a real burden on the society. So the main question is how these companies try to legitimize their behaviour through their CSR actions? Methodology: Structured, qualitative comparison of the CSR communication of the four biggest Hungarian brewers has been made. Information provided on the homepage is tested as the main and most easily available source for concerned customers. Results: Significant difference can be seen among the examined brewers in their CSR activities and its communication. Some breweries which are subsidiaries of big international companies have CSR policy at corporate level but they are not actually translated it into local initiatives. The increased amount of alcohol-free beer offered and sold is a positive trend. Conclusions and Implications: Proving legitimacy of their activity is the central element of CSR communication, but responsibility-taking is mainly perceived as a role of the consumer or the employees but not for the company itself. Keywords: Beer manufacturer, CSR, qualitative research, ethical responsibility